The global FDI network: Searching for ultimate investors - Jannick Damgaard; Thomas Elkjær (Danmarks Nationalbank, 2017)
This paper addresses three types of geographical decoupling in foreign direct investment (FDI), i.e., challenges when using traditional FDI data as a proxy for real economic integration between economies: (i) large bilateral asymmetries between inward and outward FDI, (ii) the role of special purpose entities (SPEs), and (iii) the effect of moving from immediate counterpart economy to ultimate investing economy (UIE). A unique global FDI network is estimated, where SPEs are removed andFDI positions are broken down by the UIE. Total inward FDI in the new network is reduced by onethird, and financial centers are less dominant. – – Dette papir adresserer tre former for geografisk afkobling i direkte investeringer, FDI, dvs. udfordringer, når traditionelle FDI-data benyttes som indikator for realøkonomisk integration mellem økonomier: (i) bilaterale asymmetrier mellem indadgående og udadgående FDI, (ii) gennemløbsinvesteringers rolle og (iii) effekten af at gå fra umiddelbart til ultimativt modpartsland. Der estimeres et unikt globalt FDI-netværk, hvor gennemløbsinvesteringer fjernes, og indadgående FDI-beholdninger nedbrydes i henhold til det ultimative modpartsland. De totale indadgående FDI-beholdninger i det nye netværk reduceres med en tredjedel, og finansielle centre er mindre dominerende.
Keywords: F21; F23; F30; 330; FDI; multinational enterprises; special purpose entities; financial globalization